Diversity of and initiatives for hypertension management in Asia—Why we need the HOPE Asia Network. Issue 3 (26th November 2019) - Kario, Kazuomi; Chia, Yook‐Chin; Sukonthasarn, Apichard; Turana, Yuda; Shin, Jinho; Chen, Chen‐Huan; Buranakitjaroen, Peera; Nailes, Jennifer; Hoshide, Satoshi; Siddique, Saulat; Sison, Jorge; Soenarta, Arieska Ann; et al.
Abstract: The Hypertension Cardiovascular Outcome Prevention and Evidence in Asia (HOPE Asia) Network was set up to improve the management of hypertension in Asia with the ultimate goal of achieving "zero" cardiovascular events. Asia is a diverse continent, and the prevalence of hypertension has increased over the last 30 years. There are a number of Asia‐specific features of hypertension and hypertension‐related cardiovascular complications, which means that a region‐specific approach is needed. White‐coat hypertension will become more of an issue over time as Asian populations age, and masked hypertension is more prevalent in Asian than in Western countries. Identifying and treating masked hypertension is important to reduce cardiovascular risk. Abnormal patterns of blood pressure (BP) variability common in Asia include exaggerated early morning BP surge and nocturnal hypertension. These are also important cardiovascular risk factors that need to be managed. Home blood pressure monitoring (HBPM) is an important tool for detecting white‐coat and masked hypertension, and monitoring BP variability, and practices in Asia are variable. Use of HBPM is important given the Asia‐specific features of hypertension, and strategies are needed to improve and standardize HBPM usage. Development of HBPM devices capable of measuring nocturnal BP along with other information and communication technology‐based strategies are key developments in the widespread implementation of anticipation medicine strategies to detect and prevent cardiovascular events in patients with hypertension. Region‐wide differences in hypertension prevalence, control, and management practices in Asia highlight the importance of information sharing to facilitate best practices.